Species delimitation of rice seed bugs complex: Insights from mitochondrial genomes and ddRAD‐seq data - Dong, Xue; Yi, Wenbo; Zheng, Chenguang; Zhu, Xiuxiu; Wang, Shujing; Xue, Huaijun; Ye, Zhen; Bu, Wenjun (Zoologica scripta, 2022)
Species delimitation is very important for the study of taxonomy and is essential for pest control and management. Our study focussed on the species delimitation of five Leptocorisa species (Insecta: Hemiptera: Alydidae: Leptocorisa) from China, especially for the rice seed bugs (Leptocorisa acuta species complex) due to their extreme morphological similarities. We applied multifarious distance‐based and tree‐based methods for species delimitation in the L. acuta species complex based on the multilocus genetic markers (i.e. cytochrome oxidase subunit I (cox1), whole mitochondrial genomes (WMGs) and double‐digest restriction site‐associated DNA sequencing (ddRADseq)). Both cox1 and WMGs failed to distinguish the two recent divergent taxa in the L. acuta species complex (L. chinensis and L. oratoria). However, genome‐wide nuclear SNP data unambiguously identify two separate species, which were congruent with the morphological species assignments. In addition, the morphological characters used for identification are diagnostic and stable. For the observed mito‐nuclear discordance pattern between L. chinensis and L. oratoria, mitochondrial introgression resulting from hybridization was probably inferred as the most likely explanation, which needed to expand the sampling range of the two species for further analysis. This study first provided molecular evidence for the delimitation of rice seed bugs complex, which was essential for further studies of ecology and pest management of these important rice pests.